The state of the duodenal villi in rats under epichlorohydrin and drugs influence - Smirnov, A. S.; Mirzebasov, M. A.; Smirnov, S. M. (Zaporozhye Medical Journal, 2019)
Introduction. The modern environment is polluted by xenobiotics which can cause the development of pathological processes. One of xenobiotics is epichlorohydrin (ECH). The impact of this xenobiotic causes changes in the state of various organs, including the organs of the digestive system. However, the effects of ECH on the duodenum have not been investigated. The aim of the study is to investigate the changes in the state of the duodenal villi in rats and changes in mitotic activity of mucous epithelial cells under ECH influence as well as to evaluate a possibility and effectiveness of Echinacea purpurea (EP) extract and thiotriazoline use for these changes correction. Material and methods. An experimental study was performed on male white rats. Six experimental groups were created. Six rats from each experimental group were removed from the experiment on the 1st, 7th, 15th, 30th, 60th days after the end of the two-month administration of ECH, EP extract and thiotriazoline. The height of the villi of the duodenal mucosa and changes in mitotic activity of mucous epithelial cells were estimated using a microscope of the MS 100 series of Micros (Austria). Results. Morphofunctional organization of duodenal mucosa in rats was changed after the long-term introduction of ECH. The height of villi and mitotic activity of mucous epithelial cells were reduced. Over time, the expressiveness of the changes diminished. Introduction of EP extract and thiotriazoline administration to rats which did not receive ECH was accompanied by an increase in the height of villi. In the case of thiotriazoline administration, this effect was longer. The use of EP extract as well as the use of thiotriazoline during ECH inhalations reduced the severity and duration of the decrease in the height of villi and mitotic activity of mucous epithelial cells caused by this chemical. The negative effects of ECH were corrected more effectivelly by thiotriazoline than by EP extract. Conclusions. Prolonged action of ECH is accompanied by negative changes in the state of duodenal mucosa. The negative effects of ECH were corrected more effectivelly by thiotriazoline than by EP extract.